Rab5b-Associated Arf1 GTPase Regulates Export of N-Myristoylated Adenylate Kinase 2 From the Endoplasmic Reticulum in Plasmodium falciparum - Taku, Izumi; Hirai, Tomohiro; Makiuchi, Takashi; Shinzawa, Naoaki; Iwanaga, Shiroh; Annoura, Takeshi; Nagamune, Kisaburo; Nozaki, Tomoyoshi; Saito-Nakano, Yumiko (Frontiers in Cellular and Infection Microbiology, 2021)
Plasmodium falciparum extensively remodels human erythrocytes by exporting hundreds of parasite proteins. This remodeling is closely linked to the Plasmodium virulence-related functions and immune evasion. The N-terminal export signal named PEXEL (Plasmodium export element) was identified to be important for the export of proteins beyond the PVM, however, the issue of how these PEXEL-positive proteins are transported and regulated by Rab GTPases from the endoplasmic reticulum (ER) to the cell surface has remained poorly understood. Previously, we identified new aspects of the trafficking of N-myristoylated adenylate kinase 2 (PfAK2), which lacks the PEXEL motif and is regulated by the PfRab5b GTPase. Overexpression of PfRab5b suppressed the transport of PfAK2 to the parasitophorous vacuole membrane and PfAK2 was accumulated in the punctate compartment within the parasite. Here, we report the identification of PfRab5b associated proteins and dissect the pathway regulated by PfRab5b. We isolated two membrane trafficking GTPases PfArf1 and PfRab1b by coimmunoprecipitation with PfRab5b and via mass analysis. PfArf1 and PfRab1b are both colocalized with PfRab5b adjacent to the ER in the early erythrocytic stage. A super-resolution microgram of the indirect immunofluorescence assay using PfArf1 or PfRab1b- expressing parasites revealed that PfArf1 and PfRab1b are localized to different ER subdomains. We used a genetic approach to expresses an active or inactive mutant of PfArf1 that specifically inhibited the trafficking of PfAK2 to the parasitophorous vacuole membrane. While expression of PfRab1b mutants did not affect in the PfAK2 transport. In contrast, the export of the PEXEL-positive protein Rifin was decreased by the expression of the inactive mutant of PfRab1b or PfArf1. These data indicate that the transport of PfAK2 and Rifin were recognized at the different ER subdomain by the two independent GTPases: PfAK2 is sorted by PfArf1 into the pathway for the PV, and the export of Rifin might be sequentially regulated by PfArf1 and PfRab1b.